2017
DOI: 10.1080/17512433.2018.1412826
|View full text |Cite
|
Sign up to set email alerts
|

Adhering to the principles of clinical pharmacology - the correct fixed combinations of antihypertensive drugs

Abstract: Hypertension is one of the primary modifiable risk factor for cardiac and renal diseases with the prevalence around 30-45% of the general population, with a steep increase with ageing. The administration of blood pressure-lowering drugs is to reduce the risk of major clinical cardiovascular outcomes. Hypertension guidelines recommend combination therapy in patients with high cardiovascular risk and with subclinical organ damage as well as when monotherapy fails. Areas covered: As the etiology of essential hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Combination therapies present different advantages as elsewhere reviewed (33). First, they have a synergistic effect, thus the efficacy is thought to be higher compared to the sum of single drugs.…”
Section: Combination Therapy With New Lipid Lowering Drugs: Ezetimibementioning
confidence: 99%
“…Combination therapies present different advantages as elsewhere reviewed (33). First, they have a synergistic effect, thus the efficacy is thought to be higher compared to the sum of single drugs.…”
Section: Combination Therapy With New Lipid Lowering Drugs: Ezetimibementioning
confidence: 99%
“…It is well known that the diagnosis of hypertension is traditionally defined by the clinic BP [22][23][24]. Prior randomized clinical trials and metaanalysis have consistently demonstrated that reducing clinic BP can improve cardiovascular outcomes [25][26][27][28][29]. With the advent and advancement of 24 h ABPM, out-of-clinic BP can be captured and used for evaluating daytime and nighttime BP changes [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained with losartan in T2DM patients with LVH (but without known CVD) in the Losartan Intervention For Endpoint reduction (LIFE) study [68]. Of note, fixed combinations of antihypertensive drugs and/or polypills containing aspirin, statin and one or more antihypertensive medication may represent a cost-effective strategy for CVD prevention, also improving patients’ adherence to treatment and thus achievement of therapeutic goals [6971].…”
mentioning
confidence: 55%